Analisis Kemampuan Literasi Numerasi Siswa Ditinjau dari Instrumen Asesmen Kompetensi Minimum (AKM) dengan Stimulus Berbasis Pendekatan TPACK dan Etnosains pada Materi Termokimia Kelas XI SMAN 4 Surakarta - Tasya Asokawati (LPPM Universitas Negeri Jakarta, 2025)
This purpose of this study is to improve students communication and team work skills using the 7E Learning Cycle model in learning chemistry. The subjects were 33 students of class XI IPA 2 at SMAN 43. Research conducted by the importance of communication and team work skills as life skills of the students. Based on a preliminary analysis, needs to improved students communication and team work skills. The method used in this study is a collaborative action research. Model 7E Learning Cycle consists of stages elicit, engange, explore, explain, elaborate, evaluate , and extend. This study aims to test the feasibility of the Minimum Competency Assessment (AKM) questions based on ethnoscience with the TPACK approach on thermochemistry material to measure the numeracy literacy of class XI students of SMAN 4 Surakarta, in terms of reliability, discrimination power, and level of difficulty; and to analyze students' numeracy literacy abilities based on the results of the AKM instrument measurements. This study uses a qualitative descriptive method with a purposive sampling technique and involves 100 students. Data collect ion was carried out through tests and interviews, while instrument analysis was carried out with content validity by two validators and Rasch Model analysis using Winstep software. The results showed that the AKM instrument was declared feasible to use with an item reliability value of 0.97 (excellent category), person reliability of 0.73 (sufficient), and Cronbach's alpha of 0.74 (good). The discrimination power showed that 60% of the items were fit and 40% of the items were not fit, and the level of difficulty was evenly divided from very difficult to easy. The results of student abilities showed that 31% were classified as proficient, 40% proficient, 23% basic, and 6% needed special intervention. These findings indicate that the developed instrument is effective in measuring variations in students' numeracy literacy abilities in the context of ethnoscience and the TPACK approach.